2004
DOI: 10.1556/aagr.52.2004.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of date of transplanting and nitrogen on productivity and nitrogen use indices in hybrid and non-hybrid aromatic rice

Abstract: A field experiment was carried out during the rainy (kharif) season of 2001 at the experimental farm of the Indian Agricultural Research Institute, New Delhi, India, to study the effect of date of transplanting and nitrogen on yield attributes, yields, nutrient accumulation and nitrogen use efficiencies in hybrid and non-hybrid aromatic rice. The experiment consisted of 9 treatments with 2 varieties (Pusa Basmati 1 and Pusa Rice Hybrid 10), 3 transplanting dates (3, 10 and 17 July, 2001) and 4 nitrogen levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 3 publications
14
8
0
Order By: Relevance
“…Increasing fertilizer levels did not lead to heavy grains because the sink capacity (i.e., spikelet number) was high in the cultivars during both years. These findings agreed with previous research [12,[18][19][20]. A high number of panicles per m 2 and the number of filled grains per panicle will increase grain yields.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increasing fertilizer levels did not lead to heavy grains because the sink capacity (i.e., spikelet number) was high in the cultivars during both years. These findings agreed with previous research [12,[18][19][20]. A high number of panicles per m 2 and the number of filled grains per panicle will increase grain yields.…”
Section: Discussionsupporting
confidence: 93%
“…It promotes rapid growth and increases leaf size, spikelet number per panicle, percentage of filled spikelet in each panicle and grain protein content [10][11][12][13][14] also indicated that the grain yield of most rice hybrids significantly increased when N-fertilizer went up to 180 kg ha −1 . Lin et al [15][16][17][18][19][20][21][22] found that the system of rice intensification (SRI) can significantly reduce N-fertilizer use due to planting hybrid seed at low density. High fertilizer levels also extended the vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…ammoniavolatilization, denitrification, leaching in submerged soil and runoff losses (Prasad and Power, 1995;Prasad et al, 1998;Prasad, 2005). The low AE of applied N in green manuring plots was due to N contributed by summer green manuring crops (Singh et al, 2004). The positive effect of applied Zn on grain yield caused an increase in AE of applied N.…”
Section: Discussionmentioning
confidence: 99%
“…However, T 1 (SRI + 7 th July + 100% RDN through Urea) and T 2 (SRI + 7 th July + 75% RDN through Urea + 25% RDN through PM) were found to be statistically at par with treatment T 3 (SRI + 7 th July + 50% RDN through Urea + 50% RDN through PM). This might be owing to longer growing period of the crop for better development of parts to allocate greater accumulation of photosynthates in early planting, resulting in the better development of growth and yield attributes (Singh et al, 2004).…”
Section: Number Of Effective Tillers Hill -1mentioning
confidence: 99%